2017
DOI: 10.1111/exd.13358
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method for gene knock‐down by RNA interference in human skin mast cells

Abstract: Mast cells (MCs) from human skin have been notoriously resistant to gene manipulation, and a method to knock‐down gene expression in in situ differentiated MCs is highly desired. The Dharmacon Accell® transfection system proved successful on several “difficult‐to‐transfect” cells. In the present work, we therefore tested this method on skin‐derived MCs using different siRNA entities. The siRNA was readily taken up, followed by pronounced, specific reduction of gene and protein expression. Hence, we present the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Specific inhibitors of both kinases revealed that p38, but not JNK, was implicated in the regulation of HDC and histamine by IL-33. We recently established the method of Accell-assisted RNA interference as a knock-down method in hard-to-transfect tissue-derived MCs (Hazzan et al, 2017b). By eliminating JNK and p38 expression, we confirmed that p38, but not JNK was implicated in HDC and histamine regulation.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Specific inhibitors of both kinases revealed that p38, but not JNK, was implicated in the regulation of HDC and histamine by IL-33. We recently established the method of Accell-assisted RNA interference as a knock-down method in hard-to-transfect tissue-derived MCs (Hazzan et al, 2017b). By eliminating JNK and p38 expression, we confirmed that p38, but not JNK was implicated in HDC and histamine regulation.…”
Section: Discussionmentioning
confidence: 66%
“…Accell-mediated small interfering RNA (siRNA) selfdelivery has recently been introduced as a method to perturb endogenous levels of proteins in tissue MCs (Hazzan et al, 2017a(Hazzan et al, , 2017b. Exploiting this advancement, we employed JNK1-specific and p38a-specific RNA interference to eliminate their expression after verification that these were the major isoforms expressed in skin MCs (Motakis et al, 2014).…”
Section: Il-33 Reinforces Histamine Production In a P38-dependent Butmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA interference in MCs was performed according to an established protocol [24,35,36] using the Accell ® siRNA technology (Dharmacon, Lafayette, CO, USA). Briefly, MCs were washed with 1 × Accell siRNA medium (supplemented with Non-Essential Amino Acids and L-Glutamine), plated at 1 × 10 6 /mL in Accell siRNA medium and treated with 1 µM JNK-targeting siRNA (E-003514-00-0010) or non-targeting siRNA (D-001910-10-50, serving as control) for 48 h. After incubation, cells were treated with or without IL-33 for the times indicated.…”
Section: Methodsmentioning
confidence: 99%
“…endothelial cells, hematopoietic cells, and hippocampal and cortical neurons), [3][4][5][6][7] mast cells, 8 and natural killer cells. 1,9 Ongoing experiments with siRNA indicate that macrophages also belong to these cell types (unpublished result).…”
mentioning
confidence: 99%